Predictive value of serum sortilin, HMGB1, and galanin-like peptide for gestational diabetes mellitus in women with polycystic ovary syndrome - Li, Hui; Zhao, Xinghao (Frontiers in Endocrinology, 2025)
BackgroundPolycystic ovary syndrome (PCOS) is associated with increased risk of gestational diabetes mellitus (GDM), but reliable early predictive biomarkers remain lacking. This study investigated the predictive value of serum Sortilin, HMGB1, and galanin-like peptide (GALP) for GDM development in PCOS pregnancies.MethodsThis prospective cohort study enrolled 139 PCOS patients. Serum Sortilin, HMGB1 and GALP levels were measured by ELISA at 8-12 weeks. GDM was diagnosed at 24-28 weeks using 75g OGTT (IADPSG criteria). Predictive performance was assessed using multivariable logistic regression and receiver operating characteristic (ROC) curve analysis, with adjustment for maternal age, BMI, and lipid profiles.ResultsThe PCOS-GDM group (n=60) showed significantly higher levels of all biomarkers versus controls (n=79) (all p<0.001). GALP (aOR=1.55, 95%CI:1.05-1.92) and HMGB1 (aOR=1.65, 95%CI:1.50-1.79) independently predicted GDM after adjustment. The combined model achieved superior prediction (AUC=0.84, 95%CI:0.74-0.94) versus individual markers.ConclusionSerum GALP and HMGB1 are promising early predictors of GDM in PCOS pregnancies, with combined assessment offering optimal risk stratification. These findings may facilitate timely intervention in high-risk populations.